Study of lipid lowering effects of oral antidiabetic drugs in type 2 diabetes mellitus patients - E., Shashikala; Motgi, Somnath; B. N. V., Raghawa Rao; Sattar, Mohd Abdul (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Type 2 diabetes mellitus (T2DM) is one of the most common non-communicable diseases associated with ‘atherogenic dyslipidemia’ The treatment of T2DM often is initiated with oral antidiabetic drugs, most of which not only decrease blood sugar levels effectively but also decrease the lipid levels. Hence the current study is aimed to determine the effectiveness of oral hypoglycemic agents in dealing with associated dyslipidemia. Methods: 150 T2DM patients were divided equally into five groups depending upon the oral antidiabetic drugs they received in solo or in combination for 24 weeks, with equal number of males and females in each group. After the written consent, a detail clinical history, clinical examination, Biochemical investigations including, glycosylated haemoglobin and lipid profile, chest X-ray and ECG were done. Results: After 24 weeks of study, the mean total cholesterol and mean triglycerides decreased significantly (p <0.05 to p <0.01) with monotherapy of metformin and teneligliptin as well as with combination of either metformin and glimepiride or metformin and teneligliptin. The decrease of LDL-C and VLDL-C was not statistically significant with any of the OAD drugs in solo or in combination. Similarly, HDL-C increased significantly (p <0.05) in Group I, III, IV and V; but was most effective with combination therapy. The atherogenic index of plasma also decreased (p <0.05) with metformin or its combination with either teneligliptin or glimepiride. Conclusions: Oral antidiabetic drugs are not only affordable and effective hypoglycemic agents but can also decrease serum lipids and thereby aids in the prevention and management of atherosclerosis and its complications in T2DM.